Study on Exosomes Promoting the Osteogenic Differentiation of ADSCs in Graphene Porous Titanium Alloy Scaffolds - Sun, Xu; Yang, Shude; Tong, Shuang; Guo, Shu (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium and titanium alloys (Ti6Al4V, Ti) have been widely used in bone tissue engineering to repair maxillofacial bone defects caused by traumas and tumors. However, such materials are also bio-inert, which does not match the elastic modulus of bone. Therefore, different surface modifications have been proposed for clinical application. The graphene-coated porous titanium alloy scaffold (Gr-Ti) not only reduces the elastic modulus of the material but also promotes cell adhesion and migration. Adipose-derived stem cells (ADSCs) have strong multi-directional differentiation potential with high application value in tissue repair. Exosomes (Exos) play a regulatory role as extracellular vesicles in many physiological processes. Based on the use of traditional titanium alloy in the field of bone repair defects, we prepared a compound Gr-Ti scaffold with ADSC-derived Exos. The results showed that Gr-Ti scaffolds have low toxicity and good biocompatibility, which can promote the adhesion and osteogenic differentiation of ADSCs. Exos played a role in promoting osteogenic differentiation of ADSCs related to the Wnt signaling pathway. Lastly, Gr-Ti scaffolds with ADSCs and ADSC-derived Exos successfully repaired rabbit mandibular defects. This study provides a theoretical basis for the research and development of new clinical bone repair materials.